Propidium Monoazide Integrated with qPCR Enables the Detection and Enumeration of Infectious Enteric RNA and DNA Viruses in Clam and Fermented Sausages - Quijada, Narciso M.; Fongaro, Gislaine; Barardi, Célia R. M.; Hernández, Marta; Rodríguez-Lázaro, David (Frontiers in Microbiology, 2016)
The increase of foodborne viral outbreaks highlights the need for a rapid and sensitive method for the prediction of viral infectivity in food samples. This study assesses the use of propidium monoazide (PMA) coupled with real-time PCR methods (RT-qPCR or qPCR for RNA or DNA viruses, respectively) in the determination of viral infectivity in complex animal-related food matrices. Clam and Spanish fermented sausage (“chorizo”) samples were spiked with infectious and heat-inactivated human adenovirus-2 (HAdV-2) and mengovirus (vMC0). PMA-qPCR/RT-qPCR discriminated infective virus particles, with significant reductions (>2.7 log10 or 99.7%). Additionally, infectious HAdV-2 and vMC0 were quantified by plaque assay (in plaque forming units, PFU), and compared with those in virus genomes copies (GCs) quantified by PMA-qPCR/RT-qPCR. A consistent correlation (R2 > 0.92) was showed between PFU and GCs along serial ten-fold dilutions in both DNA and RNA virus and in both food matrices. This study shows the use of PMA coupled to qPCR/RT-qPCR as a promising alternative for prediction of viral infectivity in food samples in comparison to more expensive and time-consuming methods and for those viruses that are not able to grow under available cell culture techniques.